The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0104-66322010000400016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of dry-film biocides on paint film preservation using neural networks

Abstract: -Biocides play an important role in the preservation of a variety of products susceptible to microbiological growth such as paint, a material that can undergo microbial deterioration both in storing (inside the can) and after the application on a surface. In this work, artificial neural networks were used to predict the level of fungal growth on surfaces painted with water-based paints with biocide formulations containing different concentrations of ten kinds of commercial and experimental chemical agents. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Roden (2010) [7] reported the importance of biocides in paints to resist the fungal growth. Similar observation was also made by Content et al (2010) [10]. Paint No 3 and Paint No 4 showed some amount of growth of fungi even though they contained biocides.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Roden (2010) [7] reported the importance of biocides in paints to resist the fungal growth. Similar observation was also made by Content et al (2010) [10]. Paint No 3 and Paint No 4 showed some amount of growth of fungi even though they contained biocides.…”
Section: Resultssupporting
confidence: 87%
“…The choice of a suitable biocide and its optimum dosage require knowledge of the micro-organisms that may grow. Biocides play an important role in the preservation of materials susceptible to microbiological growth [10].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is validated by the findings of Shirakawa et al (2011) that posited that buildings that are painted along the Atlantic coast will experience defects earlier than those at the hinterland. Nepal and Rai (2010), Contant et al (2010) and Hua-Tzu and Hong-Hsiang (2010) agree with this finding with the assertion that paints used as exterior finish in the coastal area are under constant attack of salt which will aggravate defects and failure. Discolouration constitutes more problems in Zone A than Zone B, likewise general accelerated failure.…”
Section: Data Analysis Results and Discussionmentioning
confidence: 64%
“…Enzymes catalyzing the degradation of protein and cellulosic thickeners may be introduced into the paint through contaminated raw materials, storage tanks, and other equipment or be released by bacteria (and less frequently, yeast) growing actively in the liquid paint (El-Sayed et al, 1996).The susceptibility of paint films to attack by microorganisms is determined in part by the chemical nature of the non volatile binder, the choice of pigmentation, and the pigment volume concentration. To a much greater degree, however, the susceptibility or resistance of a paint film to a biological attack is determined by the presence and concentration of antimicrobial agents (Contant et al, 2010).Previous studies have revealed that biocides can enhance the shelf life of paints (Voulvouliset al, 2000;Albanis et al, 2002;Martinez et al, 2001).However, public health and environmental concerns have limited the use of biocides as many bacterial strains develop resistance and require higher than safety level doses to kill microbes. Therefore, in this study, we report a rare study focusing on the preservative potential of crude soot in water based paints in relation to painting physicochemical parameters with a view to developing an environmentally friendly and cost-effective formulation technology.…”
Section: Introductionmentioning
confidence: 99%